The hard facts of the Grimms' fairy tales - Tatar, Maria (Princeton University Press, 2003)
"Murder, mutilation, cannibalism, infanticide, and incest: the darker side of classic fairly tale figures as the subject matter for this study of Jacob and Wilhelm Grimm's Nursery and Household Tales. This updated and expanded second edition includes a new preface and an appendix containing new translations of six tales, along with commentary by Maria Tatar.